Chemotherapy Plus Radiotherapy Versus Chemotherapy Alone for Patients With Peripheral T-Cell Lymphoma, Not Otherwise Specified - Chen, Zegeng; Huang, He; Li, Xiaoqian; Fang, Xiaojie; Wang, Zhao; Hong, Huangming; Zhang, Zhihui; Cai, Qingqing; Li, Zhiming; Chen, Meiting; Yao, Yuyi; Pan, Fei; et al. (Frontiers in Oncology, 2021)
Purpose Peripheral T-cell lymphoma, not otherwise specified (PTCL-NOS) is a clinically and biologically heterogeneous disease with poor prognosis. As the role of radiation therapy (RT) is still unclear, we carried out this study to evaluate the potential efficacy of RT in PTCL-NOS. Methods Patients diagnosed with PTCL-NOS between 2000 and 2016 were identified from the Surveillance, Epidemiology, and End Results (SEER) database. Propensity score matching was used to balance the characteristics between patients who received radiotherapy and those who did not receive radiotherapy. In addition, we validated the findings in an external validation cohort retrospectively recruited from two high-capacity cancer center in China between 2006 and 2016. Kaplan-Meier curves and Cox regression models were used for survival analysis. Results Of the 2768 patients with chemotherapy records in the SEER cohort, 27.6% of 844 patients with early-stage disease and 6.8% of 1924 patients with advanced-stage disease received RT. The application of RT was significantly associated with an improvement in overall survival (5-year OS rate 58.5% versus 35.1%, P <0.001) and disease-specific survival (5-year DSS rate 66.3% versus 44.0%, P <0.001) in the early-stage subgroup, while no apparent survival benefit of adding RT was identified in patients with advanced-stage disease (5-year OS rate 28.7% versus 24.4%, P = 0.089; 5-year DSS rate 32.9% versus 31.3%, P = 0.223). After adjustment, a matched cohort of 1044 patients (348 in the RT combined with CT group and 696 in the CT alone group) was created. And RT was still significantly associated with a survival benefit in the early-stage subset, but not in the advanced-stage disease group. In the validation cohort with more comprehensive data, RT also significantly improved the survival of early-stage PTCL-NOS patients. Conclusion Adding RT was associated with significant improvement in survival in early-stage PTCL-NOS, but the survival benefit of RT was not obvious in advanced-stage disease. The incorporation of RT for treatment in early-stage PTCL-NOS should be highly considered. Further prospective studies with more comprehensive data are needed to evaluate the effectiveness and toxicity of RT in PTCL-NOS.